All-printed point-of-care immunosensing biochip for one drop blood diagnostics. Issue 16 (4th July 2022) - Chi, Jimei; Wu, Yuanbin; Qin, Feifei; Su, Meng; Cheng, Nan; Zhang, Jiabing; Li, Chunbao; Lian, Zewei; Yang, Xu; Cheng, Lijun; Xie, Hongfei; Wang, Huadong; et al.
Abstract : An all-printed nanophotonic biochip is demonstrated for fast and easy-to-use quantitative detection of cardiac biomarkers. One drop of blood allows specific detection in 10 min. This is a potential platform for portable clinical diagnostics and home medical monitoring. Abstract : Designing and preparing a fast and easy-to-use immunosensing biochip are of great significance for clinical diagnosis and biomedical research. In particular, sensitive, specific, and early detection of biomarkers in trace samples promotes the application of point-of-care testing (POCT). Here, we demonstrate an all-printed immunosensing biochip with the characteristics of hydrodynamic enrichment and photonic crystal-enhanced fluorescence. Direct quantitative detection of cardiac biomarkers via one drop of blood is achieved in 10 min. After simulating the hydrodynamic behavior of one droplet serum on the printed assay, creatine kinase-MB (CK-MB) has been recognized and located on the photonic crystal arrays. Benefiting from the fluorescence enhancement effect, quantitative detection of CK-MB has been demonstrated from 0.01 ng ml −1 to 100 ng ml −1, which is superior to the conventional enzyme-linked immunosorbent assay (ELISA). This strategy provides a general and easy-to-use approach for fast quantitative detection of biomarkers, which would be improved further for portable clinical diagnostics and home medical monitoring.